ANALISIS KAJIAN INVESTASI PADA IMPLEMENTASI GREEN BUILDING DALAM UPAYA EFISIENSI BIAYA OPERASIONAL DAN KEUNGGULAN BERSAING GEDUNG PERKANTORAN (Studi Kasus pada Gedung Graha CIMB Niaga, Jakarta) - Giovanni, Erika (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims at analyzing investment appraisal in green building implementation in the attempt of attaining operational cost efficiency and creating competitive advantage of office building. This study uses the case of Graha CIMB Niaga office building, located at Sudirman Central Business District (SCBD) in Jakarta, as the object. The building is the first and only office building in Indonesia holding Platinum Green Mark award from Building Construction Authority (BCA) of Singapore. The information and the data of this qualitative case study were gathered from interviews on the management and senior officers, from secondary data – such as company’s financial data and independent survey of international property consultant, and from field observation on its implementation. The study indicates that: (1) based on cost efficiency analysis on the operational cost of the building management, the investment in green building implementation at Graha CIMB Niaga can save energy, so its operational cost will be more efficient; (2) based on competitive advantage analysis, investment in green building implementation can be seen as a competitive strategy that differentiates Graha CIMB Niaga Building with other office buildings and gives uniqueness that attracts potential tenants.Keywords: green building, BCA green mark criteria, investment in green building, Life Cycle Costs (LCC), payback period, cost saving, operational cost of building management, energy efficiency, competitive advantage